Improved purification protocol for recombinant human leukocyte antigens using an affinity magnetic agarose - Thu Zar Ma Ma Moe Min; Phanabamrung, Sonwit; Leelayuwat, Chanvit (Archives of Allied Health Sciences, 2023)
Anti-human leukocyte antigen (HLA) antibodies are a risk factor for graft failure and graft loss in organ transplantation. To develop a new biomolecular technique for anti-HLA antibody detection against HLA antigens, a large quantity of HLA proteins is necessary. The optimization of existing protein purification protocols plays a crucial role in laboratory practice in biomolecular technology. In this work, we presented the efficient expression of recombinant HLA-A and -B proteins in the HEK 293T cell line and an improved protocol of the PierceTM anti-DYKDDDDK magnetic agarose method for HLA protein purification to enhance the quantity of proteins. The percent recoveries of HLA-A and -B proteins were 81.15% and 80.73% at 350–380 μg/mL in the total eluates, respectively. The number of elution times and incubation time in the elution step were the most important to enhance the percent recovery and quantity of purified proteins. In conclusion, the improved purification protocol enables the high-yield production of functional recombinant HLA-A and -B proteins for the establishment of an ion-sensitive field-effect transistor-based immunosensor for anti-HLA antibody detection. Moreover, it could provide a useful guideline for the expression and purification of other DYKDDDDK-tagged recombinant proteins.